PENERAPAN STRATEGI QUESTIONS STUDENT HAVE DALAM PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIII.2 SMP NEGERI 8 PEKANBARU - Astuti, Dwi; Solfitri, Titi; Heleni, Susda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract:This research is conducted based on mathematics learning outcomes of class VIII.2 students of Junior High School 8 Pekanbaru which is still under KKM (Minimum Criteria of mastery learning) that has been settled by the school that is 78. The aims of this research is to improve the learning process and improve students' mathematics learning outcomes in class VIII.2 of SMP Negeri Pekanbaru odd semester of the academic year 2016/2017 At KD (based competence) 1.3 Understanding relations and functions and on KD 1.4 Determining the value of the function. This approach of this research is classroom action research (PTK) with 2 cycles. The subjects of the study were students of class VIII.2 SMP Negeri 8 Pekanbaru consisting of 19 male students and 23 female students with heterogeneous ability. This research was conducted on September 13, 2016 until 11 October 2016. Based on the data analysis of teacher and student activity after applying the Questions Student Have strategy in copoperative learning type STAD teacher and student activities are done well and experienced improvement at each meeting. Based on the data analysis of student learning outcomes, there is an increase in student learning outcomes in each cycle. Based on the analysis of KKM achievement, the number of students who reached KKM at UH (daily test) 1 amounted to 17 peoples with percentage 40,47% and UH 2 amounted to 25 peoples with percentage of 59,52%. From this study can be concluded that the implementations Questions Student Have strategy in cooperative learning type STAD can improve the learning process and also to remind students of mathematics learning outcomes of class VIII.2 of SMP Negeri 8 Pekanbaru odd semester of academic year 2016/2017 at KD 1.3 Understanding relation and function and KD 1.4. Determining the value of the functionKey words: Mathematics learning outcome, Cooperative learning, Questions Student Have,Class action research